2019
DOI: 10.1002/cncr.32174
|View full text |Cite
|
Sign up to set email alerts
|

The effect of treatment on patient‐reported distress after breast cancer diagnosis

Abstract: Background The National Comprehensive Cancer Network (NCCN) Distress Thermometer (DT) uses a 10‐point scale (in which 0 indicates no distress and 10 indicates extreme distress) to measure patient‐reported distress. In the current study, the authors sought to examine the relationship between treatment and NCCN DT scores in patients with breast cancer over time. Methods The authors included women aged ≥18 years who were diagnosed with stage 0 to stage IV breast cancer (according to the seventh edition of the Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…7 However, psychological problems for this duration have been measured less, with the exception of a few longitudinal studies focusing on anxiety and depression. The results of those studies showed that symptoms of anxiety and depression were at high levels before cancer treatment, then either slightly declined 8,9 or increased. 10 Trajectory research found that 9% of patients were consistently anxious and depressed from pre-chemotherapy to 12 months post-chemotherapy.…”
mentioning
confidence: 99%
“…7 However, psychological problems for this duration have been measured less, with the exception of a few longitudinal studies focusing on anxiety and depression. The results of those studies showed that symptoms of anxiety and depression were at high levels before cancer treatment, then either slightly declined 8,9 or increased. 10 Trajectory research found that 9% of patients were consistently anxious and depressed from pre-chemotherapy to 12 months post-chemotherapy.…”
mentioning
confidence: 99%
“…[27] Patients with breast cancer who underwent mastectomy with reconstruction reported higher levels of distress compared with patients undergoing lumpectomy and mastectomy only. [10] Our data showed that statistically signi cant differences were noted between the surgery and chemotherapy group for nervousness, pain, and problems with bathing/dressing. Surgical treatment was a signi cant predictor of psychological distress with 3.09 times risk for psychological distress versus chemotherapy treatment.…”
Section: Discussionmentioning
confidence: 57%
“…Many studies of distress have focused on the emotional problems (e.g., anxiety, depression) and physical problems (e.g., fatigue) of distress, with little attention to treatment-related and nancial factors. [8][9][10] Financial toxicity has been de ned as objective nancial burden and subjective nancial distress experienced by cancer patients as a result of their treatment. [11] Assessment of nancial toxicity may help to build a framework for nancial counseling interventions on par with symptom management (e.g., for fatigue or pain).…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that many patients who were newly diagnosed with breast cancer had clinically significant distress levels at initial consultation after diagnosis, but that over time, distress levels eventually declined to low levels for a majority of women 4 . However, we noted significant racial/ethnic differences in levels of self‐reported distress—measured on a scale of 0 (no distress) to 10 (severe distress)—at patients' first postdiagnosis oncology appointments.…”
Section: Introductionmentioning
confidence: 78%
“…1, Table 1). 4 The median age at diagnosis was 58 years and ranged from 43 to 60 years, with the youngest group being Hispanic women (n = 23) and the oldest group being non‐Hispanic Black women (n = 258). A majority of patients were non‐Hispanic White (65.6%, n = 675), married/partnered (59.2%, n = 609), and had early‐stage (0‐I) disease (59.8%, n = 615).…”
Section: Resultsmentioning
confidence: 99%